Asymptomatic extracranial vertebral artery disease in patients with internal carotid artery stenosis - Qureshi, Adnan; Ringleb, Peter A. (Neurosurgery, 2017)
Abstract. BACKGROUND: Extracranial vertebral artery disease is seen in patients with internal carotid artery stenosis, although the clinical significance is not well understood. OBJECTIVE: To determine the prevalence and natural history of extracranial vertebral artery disease in patients with recently symptomatic internal carotid artery stenosis. METHODS: We analyzed data collected for patients with recently symptomatic internal carotid artery stenosis in the Stent-Protected Angioplasty vs Carotid Endarterectomy trial. We used Cox proportional hazards analysis to compare the relative risk of various endpoints (any stroke, ipsilateral stroke, and death) between the 3 categories of extracranial vertebral artery disease (normal/hypoplastic, moderate/severe stenosis, occlusion) adjusting for age, gender, severity of internal carotid artery stenosis at baseline (<70% and ≥70%), allocated procedure (carotid angioplasty and stent placement or carotid endarterectomy) and hypertension. RESULTS: Moderate to severe stenosis and occlusion of 1 of both extracranial vertebral arteries were diagnosed in 152 (12.9%) and 57 (4.8%) of 1181 subjects, respectively. Comparing subjects with normal or hypoplastic vertebral artery, there was nonsignificant 30%, 40%, and 50% higher risk of any stroke (hazard ratio [HR] 1.3, 95% confidence interval [CI] 0.7-2.3), ipsilateral stroke (HR 1.4, 95% CI 0.7-2.5), and death (HR 1.5, 95% CI 0.7-3.1) among subjects with moderate to severe vertebral artery stenosis after adjusting for potential confounders. CONCLUSIONS: There may be an increased risk of stroke and death in patients with symptomatic internal carotid artery stenosis with concurrent asymptomatic extracranial vertebral artery stenosis.